2016
DOI: 10.1016/j.ijpe.2016.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Towards a theory for lean implementation in supply networks

Abstract: This paper aims to investigate the supply network (SN) characteristics affecting the extension of lean programmes to SN and the interactions between lean practices and these characteristics to understand how to create more favorable conditions for lean extension programmes. A multiple case study methodology is implemented to analyze different lean programmes in SNs and different contextual conditions in which they are implemented. Three different SNs have been analyzed to provide insights on the whole value st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 50 publications
1
52
0
4
Order By: Relevance
“…Furthermore, (61.4) of the respondents showed that LSCM would reduce the wastes in their corresponding firms. These findings align with the literature (Bortolotti et al, 2016;Tortorella et al, 2017). Other benefits are displayed in Figure (8).…”
Section: Perception Of Lscm Benefits and Barrierssupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, (61.4) of the respondents showed that LSCM would reduce the wastes in their corresponding firms. These findings align with the literature (Bortolotti et al, 2016;Tortorella et al, 2017). Other benefits are displayed in Figure (8).…”
Section: Perception Of Lscm Benefits and Barrierssupporting
confidence: 91%
“…Accordingly, there are four major key practices for expanding lean programs to supply chains. These practices are: Engage suppliers, transfer leanknowledge, lean program commitment, and lean program alignment (Bortolotti et al, 2016). To implement lean techniques across the supply chain, communications beyond the company must reach to the outside actors.…”
Section: Kaizen (Continuous Improvement)mentioning
confidence: 99%
See 1 more Smart Citation
“…Further manufacturing environments investigated are aerospace (Bortolotti et al . ; Browning and Sanders ; Crute et al . ; Martínez‐Jurado and Moyano‐Fuentes ), construction (Eriksson ), semi/processing industries (e.g.…”
Section: Literature Analysismentioning
confidence: 99%
“…Instilling principles of lean and quality thinking, rather than just tools and methods, is essential to effective transference (Spear & Bowen, 1999). Since much of the soft technology is implicit, rather than explicit, collaborative efforts with close contact and working relationships fosters the transfer of CSR consciousness and principles the stage of development of the sustainability efforts and the location in the supply chain are also factors in the choice of approach and methods to employ (Bortolotti et al, 2016).…”
Section: Implementing Change In Global Supply Chains-lessons From Leamentioning
confidence: 99%